Scoring accuracy index for various attacking playing positions as a function of the attention control of futsal players - Jebur, Waheb Razzak; Jassim, Amer Saeed (International Journal of Psychosocial Rehabilitation, 2020)
Futsal is a relatively recent game that has received great attention at the global, regional and local levels, as it is one of the difficult sports that require high physical fitness, mental abilities at a high level and a special kind of psychological preparation, as this game has witnessed a great development in achievements As a result of the continuous effort by experts and specialists, it has become a wider field and made maximum use of other sciences such as physics, physiology, anatomy, sports psychology and other sciences. Therefore, all these fields will be prepared to achieve mathematical achievement. Through the foregoing, the importance of research lies in knowing the relationship between the scoring accuracy index while the player performs various offensive playing situations that make him within the atmosphere of official competitive matches and his attentive control, as well as the possibility of predicting the level of accuracy index for aiming in terms of attention control.